The Effect of Compensation And Intrinsic Motivation on The Performance of Employees With Job Morale as a Mediation Variable (Study on Cooperatives in Pejaten) - Ida Ayu Dian Purnama Sari (JUSTBEST: Journal of Sustainable Business and Management, 2021)
This study aims to determine and explain the effect of compensation and intrinsic motivation on morale, to find out and explain the effect of compensation, intrinsic motivation, and morale on employee performance at Cooperatives in Pejaten Village, and to know and explain the role of work spirit in mediating the effects of compensation and intrinsic motivation on employee performance at the Cooperative in Pejaten Village. The population in this study were all employees who worked at the Cooperative in Pejaten Village, as many as 50 employees. The sampling technique used is a saturated sample (census) where the entire population is used as a sample of research, amounting to 50 people. The data used were primary data obtained from questionnaires to determine respondents' perceptions of the variables under study and secondary data obtained from documents and other information available at the Cooperative in Pejaten Village. The research hypothesis testing uses Partial Least Square (PLS) applications. The results showed that: (1) compensation has a significant positive effect on employee morale (2) intrinsic motivation has a positive and insignificant effect on employee morale (3) compensation has a positive and significant effect on employee performance (4) intrinsic motivation has a positive effect and not significant to employee performance (5) work morale has a negative and significant effect on employee performance, (6) work morale is not a mediation between compensation to employee performance (7) work morale is not a mediation between intra-motivation to employee performance.